The Effect The Effect of Product Differentiation and Customer Relationship on the Increase in Organic Fertilizer Sales in Sidoarjo Regency - Ridwan; Ferriswara, Dian; Herawati, Andry; Ayuningtiyas, Galuh Ajeng (Cita konsultindo, 2026)
This study is intended to evaluate the impact of product differentiation and customer relations on the increase in organic fertilizer sales volume in the Sidoarjo Regency area. A quantitative approach was applied through a survey involving 120 participants, namely farmers and organic fertilizer traders in the area. Sample selection was carried out by stratified random sampling technique. Information collection was carried out through a questionnaire, then processed using multiple linear regression analysis with the support of SPSS software version 25. The findings of the study revealed that product differentiation had a significant positive effect on the increase in organic fertilizer sales, with a coefficient of 0.458 (p<0.05). Similarly, customer relationships showed a significant positive impact on the increase in sales, with a coefficient of 0.412 (p<0.05). Simultaneously, product differentiation and customer relationships contributed significantly to the increase in organic fertilizer sales, with a percentage of 71.6% (R² = 0.716), while the remaining 28.4% were influenced by external variables that had not yet been explored. This study suggests that organic fertilizer makers in Sidoarjo Regency continue to innovate in product differentiation and strengthen long-term ties with consumers to encourage higher sales.